Academic Productivity at Orthopaedic Surgery Sports Medicine Fellowship Programs in the United States Has a Weak Positive Correlation With Nonresearch Lifetime Industry Earnings - Benjamin Miltenberg, M.D.; William L. Johns, M.D.; Anthony N. Baumann, D.P.T.; Faheem Pottayil, M.S.; Bradley Richey, M.D.; Albert T. Anastasio, M.D.; Kempland C. Walley, M.D.; Christopher C. Dodson, M.D.; Sommer Hammoud, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To characterize the relationship between academic productivity, as defined by the h-index, and industry payments for fellowship-trained sports medicine surgeons in faculty positions at sports medicine fellowships. Methods: The American Orthopaedic Society for Sports Medicine fellowship directory was used to create a comprehensive list of all fellowship programs nationwide. Fellowship websites were then reviewed to generate a list of the teaching faculty associated with each program. Total nonresearch lifetime earnings were obtained from the Centers for Medicare & Medicaid Services website. Academic productivity of each fellowship faculty was assessed via the h-index. Frequency counts and other descriptive statistic measures were used to describe the data for this study. Correlation was performed for continuous data using Spearman’s ρ. Results: Ninety orthopaedic surgery sports medicine fellowships were identified with a combined total of 574 orthopaedic surgery sports medicine fellowship faculty. There was a weak positive correlation between individual physician h-index and individual physician lifetime earnings at orthopaedic surgery sports medicine fellowships (P < .001; Spearman’s ρ = 0.329). There was a statistically significant difference between individual faculty h-index by quartile and individual faculty lifetime earnings (test statistic: 47.3; P < .001). There was no significant regional difference in payments, but there is remarkable heterogeneity in the distribution of payments to individual physicians, with the top 10% of physicians receiving over 80% of industry dollars. Conclusions: There is a positive correlation between academic productivity and industry payments at both the individual and institutional levels in orthopaedic sports medicine departments, although this relationship was greater at the fellowship level. Furthermore, the majority of nonresearch industry funding goes to a minority of physicians. Clinical Relevance: Evaluating the impact that nonresearch industry payments have on a sports medicine orthopaedic surgeon’s research productivity can offer valuable insights into the relationship between industry compensation and scholarly output in this field.